Fifty Years of Portuguese Democracy and the Third Sector: A Still Under-Recognized Field to Be Strengthened Through Academic Collaboration? - Raquel Rego; Simaens, A.; Oliveira, V. (Inside ISTR: Quarterly Members Newsletter (January - March), 2026)
Over the past fifty years, Portugal’s third sector has grown substantially and continues to expand and diversify. However, its trajectory has been far from linear. Following forty-eight years of dictatorship (1926–1974), associational life only began to develop in the final phase of the regime during the so-called Marcelista Spring. It was not until after 1974 that civil society emerged in full force, making the transition period particularly dynamic. As historians such as Pedro Ramos Pinto have demonstrated, the vibrant grassroots movements of that time were swiftly followed by a process of democratic normalization that helped shape what is now referred to as a society of mild manners. In 2026, Lisbon will host a leading international conference dedicated to the third sector, bringing together researchers from dozens of countries across all continents. It will provide an opportunity to discuss the Portuguese case, informed by comparative perspectives and international experience. The event also aims to strengthen collaboration between academia and the sector to foster joint projects and specialized training, both of which have significant growth potential. All interested participants are warmly invited to attend the 17th International Conference of the International Society for Third-Sector Research, to be held at Iscte – Instituto Universitário de Lisboa from 14 to 17 July 2026.